Efficient 1,4-addition of α-substituted fluoro(phenylsulfonyl)methane derivatives to α,β-unsaturated compounds - Prakash, G. K. Surya; Zhao, Xiaoming; Chacko, Sujith; Wang, Fang; Vaghoo, Habiba; Olah, George A. (Beilstein Journal of Organic Chemistry, 2008)
The 1,4-addition of a monofluoromethyl nucleophile to a variety of α,β-unsaturated compounds has been achieved under mild conditions using either phosphines or potassium carbonate at room temperature. α-Substituted fluoro(phenylsulfonyl)methane easily undergoes Michael addition to α,β-unsaturated ketones, esters, nitriles, sulfones, as well as propynoates at room temperature to yield the corresponding adducts in moderate to excellent yields.

Organofluorine Chemistry: Principles and Commercial Applications - Smart, B. E. (Characteristics of C-F Systems, 1994)

(untitled) - Smart, B. E. (J. Fluorine Chem., 2001)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH Verlag GmbH & Co. KGaA, 2004)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

Biomedical Frontiers of Fluorine Chemistry - Ojima, I.; McCarthy, J. R.; Welch, J. T. (American Chemical Society, 1996)

Organofluorine Compounds in Medicinal Chemistry and Biomedical Applications - Filler, R.; Kobayashi, Y.; Yagupolskii, L. M. (Elsevier, 1993)

(untitled) - Prakash, G. K. S.; Hu, J.; Olah, G. A. (J. Org. Chem., 2003)

(untitled) - Prakash, G. K. S.; Mandal, M. (J. Am. Chem. Soc., 2002)

(untitled) - Prakash, G. K. S.; Hu, J.; Mathew, T.; Olah, G. A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Prakash, G. K. S.; Mandal, M.; Olah, G. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Prakash, G. K. S.; Chacko, S.; Alconcel, S.; Stewart, T.; Mathew, T.; Olah, G. A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Prakash, G. K. S.; Weber, C.; Chacko, S.; Olah, G. A. (J. Comb. Chem., 2007)

(untitled) - Prakash, G. K. S.; Weber, C.; Chacko, S.; Olah, G. A. (Org. Lett., 2007)

Fluorine-Containing Synthons - Prakash, G. K. S.; Hu, J. (New Nucleophilic Fluoroalkylation Chemistry, 2005)

(untitled) - Prakash, G. K. S.; Yudin, A. K. (Chem. Rev., 1997)

(untitled) - Prakash, G. K. S.; Mandal, M. (J. Fluorine Chem., 2001)

(untitled) - Maruoka, K.; Shimada, I.; Akakura, M.; Yamamoto, H. (Synlett, 1994)

(untitled) - Sevenard, D. V.; Sosnovskikh, V. Y.; Kolomeitsev, A. A.; Königsmann, M. H.; Röschenthaler, G.-V. (Tetrahedron Lett., 2003)

(untitled) - Sosnovskikh, V. Y.; Usachev, B. I.; Sevenard, D. V.; Röschenthaler, G.-V. (J. Org. Chem., 2003)

(untitled) - Lefebvre, O.; Brigaud, T.; Portella, C. (Tetrahedron, 1998)

(untitled) - Sato, K.; Nakazato, S.; Enko, H.; Tsujita, H.; Fujita, K.; Yamamoto, T.; Omote, M.; Ando, A.; Kumadaki, I. (J. Fluorine Chem., 2003)

(untitled) - Sato, K.; Omote, M.; Ando, A.; Kumadaki, I. (J. Fluorine Chem., 2004)

(untitled) - Kitazume, T.; Nakayama, Y. (J. Org. Chem., 1986)

(untitled) - Bridge, C. F.; O'Hagan, D. (J. Fluorine Chem., 1997)

(untitled) - Takeuchi, Y.; Nagata, K.; Koizumi, T. (J. Org. Chem., 1989)

(untitled) - Wade, P. A.; Hinney, H. R.; Amin, N. V.; Vail, P. D.; Morrow, S. D.; Hardinger, S. A.; Saft, M. S. (J. Org. Chem., 1981)

(untitled) - Truce, W. E.; Klingler, T. C.; Paar, J. E.; Feuer, H.; Wu, D. K. (J. Org. Chem., 1969)

(untitled) - Peng, W.; Shreeve, J. M. (Tetrahedron Lett., 2005)

(untitled) - Fargeas, V.; Baalouch, M.; Metay, E.; Baffreau, J.; Ménard, D.; Gosselin, P.; Bergé, J. P.; Barthomeuf, C.; Lebreton, J. (Tetrahedron, 2004)

(untitled) - Walker, D. (J. Org. Chem., 1966)

(untitled) - Doyle, K. J.; Moody, C. J. (Tetrahedron, 1994)

(untitled) - Takeuchi, Y.; Asahina, M.; Hori, K.; Koizumi, T. (J. Chem. Soc., Perkin Trans. 1, 1988)

(untitled) - Ohta, H.; Kato, Y.; Tsuchihashi, G. (J. Org. Chem., 1987)

(untitled) - Takeuchi, Y.; Ogura, H.; Kanada, A.; Koizumi, T. (J. Org. Chem., 1992)

(untitled) - Nyffeler, P. T.; Gonzalez Durón, S.; Burkart, M. D.; Vincent, S. P.; Wong, C.-H. (Angew. Chem., Int. Ed., 2005)
For a review.

(untitled) - Fukuzumi, T.; Shibata, N.; Sugiura, M.; Yasui, H.; Nakamura, S.; Toru, T. (Angew. Chem., Int. Ed., 2006)

(untitled) - McDougal, N. T.; Schaus, S. E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Kraft, M. E.; Seibert, K. A.; Haxell, T. F. N.; Hirosawa, C. (Chem. Commun., 2005)

(untitled) - Palmelund, A.; Myers, E. L.; Tai, L. R.; Tisserand, S.; Butts, C. P.; Aggarwal, V. K. (Chem. Commun., 2007)

(untitled) - Ni, C.; Li, Y.; Hu, J. (J. Org. Chem., 2006)

(untitled) - Prakash, G. K. S.; Hu, J. (Acc. Chem. Res., 2007)